HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA TERHADAP PERILAKU PENCEGAHAN PENYALAHGUNAAN NAPZA DI SMP NEGERI 259JAKARTA TIMUR TAHUN 2014 - Rayi Rachmatsyah, (2014)
Teenagers are in the range indvidu transition through many changes physically, mentally and negative behaviors due to environmental influences such as friends and family that resulted in losses for themselves, for example drug abuse. The aim of this study is knowing the relationship between knowledge and attitude toward drug abuse preventive behaviour in SMP Negeri 259 East Jakarta. This study is characteristically descriptive and analytic, with Cross Sectional as a study design. The sample of this study are 323 people and the type of sampling is using primary data in the form of a questionnaire taken by simple random sampling method. As a result, there are 152 (47,1%) teenagers who have an average knowledge, 273 (84,5%) teenagers have a good attitude, and 191 (59,1%) teenagers have an average behaviour. A result using Chi-Square formula showed there is a relationship between knowledge with drug abuse preventive behaviour (p=0,009) and there is also a relationship between teenagers attitude toward drug abuse preventive behaviour (p=0,038).